A Comparative Evaluation of Microleakage in Class V Composite Restorations - Sujatha Gopal Sooraparaju; Pavan Kumar Kanumuru; Surya Kumari Nujella; Karthik Roy Konda; K. Bala Kasi Reddy; Sivaram Penigalapati (International Journal of Dentistry)
Aim. To compare and evaluate the microleakage in class V lesions restored with composite resin with and without liner and injectable nanohybrid composite resin. Materials and Methodology. 60 class V cavities were prepared in 30 freshly extracted teeth. After etching and application of bonding agents these cavities were divided into three groups: Group A (n=20)—restored with composite resin, Group B (n=20)—flowable composite resin liner + composite resin, and Group C (n=20)—restored with injectable composite resin. After curing all the specimens were subjected to thermocycling and cyclic loading. Specimens were stained with 0.5% basic fuchsin and evaluated for dye penetration. Results. Results are subjected to Kruskal Wallis and Wilcoxon test. Conclusion. Within the limitations of this study, none of the three materials were free from microleakage. All the three materials showed more microleakage at gingival margins compared to occlusal margins. Among all the groups G-ænial Flo showed the least microleakage at the gingival wall.